2021
DOI: 10.3389/fcell.2021.670960
|View full text |Cite
|
Sign up to set email alerts
|

LRP5 and LRP6 in Wnt Signaling: Similarity and Divergence

Abstract: The canonical Wnt/β-catenin signaling plays a fundamental role in regulating embryonic development, injury repair and the pathogenesis of human diseases. In vertebrates, low density lipoprotein receptor-related proteins 5 and 6 (LRP5 and LRP6), the single-pass transmembrane proteins, act as coreceptors of Wnt ligands and are indispensable for Wnt signal transduction. LRP5 and LRP6 are highly homologous and widely co-expressed in embryonic and adult tissues, and they share similar function in mediating Wnt sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
74
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(75 citation statements)
references
References 108 publications
(180 reference statements)
1
74
0
Order By: Relevance
“…In addition, the human Lrp6 crystal structure protein has been characterised using electron microscopy (EM) and other molecular/bioinformatic tools [ 10 , 11 , 12 , 13 , 14 , 15 ] ( Figure 2 B). LRP6-E1E2 or LRP6-E3E4 proteins were purified and concentrated for crystallisation [ 10 ].…”
Section: Lrp6 Structure and Homologymentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the human Lrp6 crystal structure protein has been characterised using electron microscopy (EM) and other molecular/bioinformatic tools [ 10 , 11 , 12 , 13 , 14 , 15 ] ( Figure 2 B). LRP6-E1E2 or LRP6-E3E4 proteins were purified and concentrated for crystallisation [ 10 ].…”
Section: Lrp6 Structure and Homologymentioning
confidence: 99%
“…Moreover, embryos die shortly after gastrulation in Lrp5+/−; Lrp6−/− mutants [ 31 ]. This study suggested a functional redundancy between Lrp6 and Lrp5, but that Lrp6 plays a more essential role in development [ 11 ]. Importantly, total inactivation of Lrp6 led to multiple abnormalities in many organs, including the heart, eyes, limbs, brain, and developing spinal cord, and resulted in perinatal mortality [ 39 , 40 ].…”
Section: Lrp6 Expression and Function During Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…However, to our knowledge, the regulation of these receptors by GSIs have not been investigated specifically within skeletal muscle. Another γ-secretase substrate, low-density lipoprotein receptor-related protein 6 (LRP6), is a transmembrane receptor crucial to canonical Wnt signaling [62,63]. Crosstalk between Notch and Wnt have been widely discussed for proper skeletal muscle regeneration, while LRP6-mTOR signaling has been investigated in cardiomyocytes of 13 and hepatocytes [1,64,65].…”
Section: Discussionmentioning
confidence: 99%
“…These changes go hand in hand with the inactivation of canonical Wnt signaling and activation of non-canonical Wnt signaling pathways (MacDonald et al, 2009;Ren et al, 2021). Furthermore, there was a synergistic effect of non-canonical Wnt5a and Wnt11 in ASMCs to induce cardiac differentiation by increasing the expression cardiac markers.…”
Section: Non-canonical Wnt Ligands Wnt5a and Wnt11 Induces Cardiogenesis And Maintains Viability After Hypoxic Injurymentioning
confidence: 99%